(untitled) (Research, Society and Development, 2020)
Reading is a basic principle for transformative education, but awakening in students a taste for the act of reading has been one of the great challenges of the educational system. In view of its importance for student education, it is up to the school to promote practices that are able to encourage reading through strategies that aim to "reframe" this practice. In this sense, this article intends to propose a reflection on the importance of active methodologies and the use of playfulness, in educational practices applied in the classroom, aiming to encourage, above all, reading. It is a qualitative research, with a case study about an educational practice with thirty students of the 2nd grade of high school, in a state school of the public network, in Morrinhos-GO. Applied practice proposed reading and rereading Machado’s tales, allowing students to better understand the texts read, in addition to valuing students’ creativity, considering their knowledge of the world and social interaction in the teaching-learning process. Thus, it was possible to conclude that investing in active methodologies and in the use of playfulness in the classroom, can contribute to the redefinition of reading, allowing a meaningful learning for the formation of new readers.